Stereodivergent access to all four stereoisomers of chiral tetrahydrobenzo[f][1, 4]oxazepines, through highly diastereoselective multicomponent Ugi–Joullié reaction. Issue 2 (3rd January 2020) - Pinna, Alessandro; Basso, Andrea; Lambruschini, Chiara; Moni, Lisa; Riva, Renata; Rocca, Valeria; Banfi, Luca
Abstract : Starting from easily accessible enantiopure 1, 2-aminoalcohols and salicylaldehydes, a concise and diastereodivergent route to tetrahydrobenzo[ f ][1, 4]oxazepines has been developed. Abstract : Starting from easily accessible chiral enantiopure 1, 2-amino alcohols and salicylaldehydes, a concise route to cyclic imines has been developed. These chiral cyclic imines undergo a highly diastereoselective Ugi–Joullié reaction to give trans tetrahydrobenzo[ f ][1, 4]oxazepines with the introduction of up to 4 diversity inputs. The cis isomer may also be attained, thanks to a thermodynamically controlled base catalysed epimerization. Free secondary amines have been obtained using an unprecedented "removable" carboxylic acid.